Evaluating the contribution of lower extremity kinetics to whole body power output during the power snatch - Lee, S.; DeRosia, K. D.; Lamie, L. M. (Sports Biomechanics, 2018)
This study evaluated the contribution of lower extremity (hip, knee and ankle) net joint torques (NJT) to whole body power (WBP) output during the power snatch (PS). Ten experienced weightlifters (five males and five females) performed five trials of the PS with 60% of one repetition maximum. Lower extremity NJT and WBP were extracted through a three-dimensional motion analyses and used for data analyses. Pearson correlation coefficients were obtained to observe the relationship between lower extremity NJT and WBP. Multiple-regression (stepwise) analyses was also conducted to evaluate the contribution of lower extremity NJT to WBP during the PS with the hip, knee and ankle NJT being the independent variables. Hip NJT was characterised as a significant positive correlation with WBP (r = 0.47, p < 0.01), while knee NJT showed a significant negative correlation with WBP (r = -0.34, p < 0.05). A significant inter-correlation was also observed between hip NJT and knee NJT (r = -0.66, p < 0.01). Hip NJT was identified as a significant contributor to WBP during the PS. Practically, this study suggested that training skills allowing weightlifters to utilise hip extensor muscle action would help to improve WBP during the PS.